Transtorno do espectro autista: assistência educacional em associações de pais e amigos dos excepcionais do interior paulista - Justino, Camila Cristina Catan (2019)
Autistic Spectrum Disorder is a general condition for a group of complex brain development disorders, before, during or shortly after birth. Environmental, genetic or physiological factors are measured at the time of diagnosis. Objective: To describe and analyze the functioning and characteristics of the Special Education Institutions of Catanduva Council to attend students with ASD. Method: A descriptive, cross - sectional, quantitative approach study carried out in 11 APAES from the Regional Council of Catanduva / SP. Data were collected through Institutionals´ questionnaires after approval from the Research Ethics Committee of the Medical School of São José do Rio Preto-SP. Results: The statistical analysis showed that 11 special education institutions were included, working on during business hours, with a mean of 111.9 students enrolled, mean minimum age of 2.8 years, and maximum of 58.3 years. From the total, 63.6% have been providing services for Intellectual Disability and Multiple Disability, 81.8% developing care in phase I schooling (6 years to 14 years and 11 months) and 72.7% in phase II with a socio-educational program (15 years to 30 years). The average number of students per room for early stimulation is 10.9. The mean number of students in phase I is 35, median 10.0 (SD: ± 68.3, minimum 0 students, maximum 236 students). In phase II the average is 20.0 students. From these, 63.6% have specific ASD care . The main teaching method used was the PECS (36.4%). Most of the institutions have specialized professional services (63.6%) and appropriate classroom (63.6%). The average of institutions with school principal was 0.9, o coordinator 1.0 per institution, specialist pedagogue the average 7.2 and specialized teacher on physical education, art and computer science, the average was 1.5. The average caregiver was 1.1 and monitor 1.5. In the health area, the main professionals were social worker (average 1,2), auxiliary or Nursing technician (average 0.3), nurse (average 0.1), physiotherapist (average 1.4), speech therapist (average 1 , median (0.9), nutritionist (mean 0.5), psychologist (mean 1.1) and occupational therapist (mean 1.2). Conclusion: Taking into account the objective of the study; we can conclude that most Special Education Institutions are prepared to attend the child with ASD and even with some disabilities; these Institutions can contribute with partnerships with regular education as well as to support the training and orientation of teaching for children with ASD.